Black-Letter Methodology in Qualitative Research: Theoretical Perspectives and Applications - Aryal, Arjun; Tripathi, Yashodham (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This article discusses the need for interdisciplinary collaboration in qualitative research and how incorporating black-letter methodology can facilitate this. Black-letter methodology, a practice that has been employed in legal research for centuries, is seldom seen in general qualitative research, which often emphasizes social research methodologies. According to this paper, the systematic examination of legal texts to comprehend legal principles and their applications, as done in black-letter methodology, can bridge the gap between law and qualitative research and contribute to a deeper comprehension of the legal determinants of quality of life. The paper delineates the fundamental attributes of blackletter methodology, including its methodology, scientific justification, data analysis techniques, and concise history. It also examines the advantages and disadvantages of this methodology. Additionally, the paper investigates the potential applications of black-letter methodology in qualitative research. It underscores its implications for the study of the legal determinants of quality of life, the enhancement of policy development, the addressing of emerging challenges, and the strengthening of qualitative research education. The article concludes by asserting that the incorporation of black-letter methodology into qualitative research curricula and practices can result in qualitative research strategies that are more effective and equitable. It urges faculty members to promote the integration of this valuable methodology to enhance qualitative research practices in Nepal and beyond.